Discrimination of stereoisomers by one‐dimensional 13C NMR: All 16 stereoisomers of 4‐hydroxy‐α‐tocopherol resolved. (23rd August 2021) - Lankhorst, Peter P.; Duchateau, Alexander L. L.; Netscher, Thomas
Abstract : All 16 resolved! A vitamin E‐derived compound containing four chiral centers is the first example where all stereoisomers, that is, eight diastereomeric pairs of enantiomers, could be discriminated in a single NMR run. Measurement at 176 MHz in the presence of Pirkle's alcohol as a chiral solvating agent is a relatively robust, simple, easy‐to‐set‐up, and fast method.